2011
DOI: 10.1007/s00134-011-2339-5
|View full text |Cite
|
Sign up to set email alerts
|

Is influenza A(H1N1) pneumonia more severe than other community-acquired pneumonias? Results of the GiViTI survey of 155 Italian ICUs

Abstract: This study confirmed the specific features of critically ill A(H1N1) patients (i.e., young age, pregnancy, obesity). The pandemic did not increase ICU workload compared with other periods. A(H1N1) pneumonia did not have a higher risk of death than CAP of different origin among patients admitted to the ICU.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
12
1
Order By: Relevance
“…These patients had considerably higher mortality rates and longer lengths of stay compared to patients without SARI. The in-hospital mortality rate in our cohort was similar to rates reported in patients with severe community-acquired pneumonia in previous studies [17,20,30]. This can be explained by the frequent occurrence of organ failure in these patients.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These patients had considerably higher mortality rates and longer lengths of stay compared to patients without SARI. The in-hospital mortality rate in our cohort was similar to rates reported in patients with severe community-acquired pneumonia in previous studies [17,20,30]. This can be explained by the frequent occurrence of organ failure in these patients.…”
Section: Discussionsupporting
confidence: 89%
“…Repeated outbreaks of SARI-related epidemics represent a major healthcare problem [1][2][3][4]. Several studies have investigated the epidemiology and clinical characteristics of SARI, with a special emphasis on viral etiology [13][14][15][16][17] or on the subset of patients admitted to the ICU with severe community-acquired pneumonia [17][18][19][20][21][22]. To the best of our knowledge, our study is the first to investigate this issue in a large prospective, multinational cohort of critically ill patients with SARI, providing a global view of this condition worldwide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial clinical picture of influenza A/H1N1 is very similar to that of seasonal influenza or even nonspecific (influenza-like) viral processes. 65,66 Its rapid evolution, with serious respiratory complications, made it necessary among other aspects to investigate which laboratory variables could help quickly identify those patients likely to suffer a poorer clinical course. 67---69 The first studies made in this sense found increased levels of lactate dehydrogenase (LDH) and creatine phosphokinase (CPK) to be more frequent in patients with confirmed influenza A/H1N1 than in those with a negative diagnosis despite the presence of similar clinical manifestations.…”
Section: Usefulness Of the Laboratory Test Findings In Assessing Sevementioning
confidence: 99%
“…The 2009 influenza A (H1N1) pandemic did not significantly affect ICU occupancy rates and, compared with community-acquired pneumonia of other origins, H1N1 pneumonia was associated with the same risk of death when potential confounders were taken into consideration [26]. However, this pandemic more commonly affected young people, many of whom developed severe respiratory failure requiring extracorporeal lung assist support.…”
Section: The Role Of Fungi and Virusesmentioning
confidence: 98%